Penerapan Budaya dalam Komunikasi Konseling yang Efektif - NELISMA, YULIANA (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2022)
The counseling process pays attention to, respects, and respects cultural elements. The alleviation of individual problems is very much possible with a culture that affects the individual. Guidance efforts in realizing the functions of education, directing efforts to help individuals to expand, renew, and integrate the value system into independent behavior. In this effort, guidance and counseling is very possible to use methods, approaches and techniques, to understand and facilitate individual development that is directed at human development in accordance with their existential nature. In society there is growing cultural diversity, so one communication approach in counseling that can be used is cross-cultural counseling communication.This study seeks to find and analyze data related to effective cross-cultural communication conducted by BK teachers at SMPN 2 Guguak District with Javanese and Minang ethnic backgrounds. This research is a field research with data collection in the form of interviews, observations and documentation. Data analysis using data reduction techniques, data presentation and conclusion.Based on the results of the study, it is known that, First: there are similarities in cross-cultural communication carried out by teachers to students with Javanese and Minang ethnic backgrounds, namely: in language use Indonesian as a means of communication, in certain cases using a clinical approach, using skills such as empathic skills , asking questions, assertive and confrontational, placing the position of teachers as friends and even parents of students, and treating students according to their rights and obligations. Second, the difference in cross-cultural communication between the two (Javanese and Minang students) is seen in the use of the approach, namely the approach for ethnic Javanese students using a rational-emotive approach, while for ethnic Minang students using a non-directive approach.